Clinical Features of Acute Rhabdomyolysis in 55 Pediatric Patients - Yao, Zhengxiong; Yuan, Ping; Hong, Siqi; Li, Mei; Jiang, Li (Frontiers in Pediatrics, 2020)
OBJECTIVE: This study was designed to compare the clinical manifestations, laboratory tests, etiology, and prognosis of children with acute rhabdomyolysis (RM) at various ages. This study was designed to analyze the risk factors for acute kidney injury (AKI) in children with RM and to identify the role of neuromuscular and autoimmune disease in children with RM. METHODS: Clinical data for 55 children with RM were collected and statistically analyzed. Patients were stratified to an infant group (G1) (age <1 yr), preschool group (G2) (age 1-6 yr), school-age group (G3) (age 7-11 yr), and an adolescent group (G4) (age 12-16 yr). RESULTS: The top three clinical manifestations were dark urine (52.7%), myalgia (38.2%), and fever (23.8%). Patients in G1 had fever (71.4%), vomiting (77.8%), and urinalysis abnormalities (14.3%), without triad clinical manifestations. Fifty percent of patients in G4 group had myalgia; 70.8% had dark urine; 75% had abnormal urine tests. The most common cause in each age group was as follows: sepsis (57.1%) in G1; hereditary neuromuscular diseases (44.4%) in G2; immune diseases (40%) in G3; strenuous exercise (50%) in G4. Logistic regression analysis shown that AKI was not corelated with age, gender, or peak creatine phosphokinase. AKI was, however, associated with presence of an electrolyte disorder. CONCLUSION: The clinical manifestations and laboratory findings in infants with acute RM are not typical and need to be taken seriously. The presence of an electrolyte disorder is a risk factor for AKI in children with RM. The most common pathogenesis of RM varies among age groups. Congenital hereditary metabolic disease and immune diseases should not be ignored as a cause of RM in children.